Tata kelola internal dan eksternal untuk mengatasi permasalahan pangan di Indonesia - Reza Hendriyantore (Jurnal Good Governance, 2017)
The effort to put good governance in development in Indonesia is basically not new. Since the Reformation, the transformation of closed government into an open government (inclusive) has begun to be pursued. Highlighting the conflicts in the land sector that tend to strengthen lately, there are some issues that have intensified conflicts in the field, such as the lack of guaranteed land rights in various legal and policy products. In this paper, a descriptive method is considered important in identifying the applicable issue and methodological framework for addressing governance issues in Indonesia. To reduce such agrarian conflicts between farmers and the government, and as an effort to increase farmers' income, all farmers are incorporated into agricultural cooperatives. Agricultural cooperatives are structured down to the National Level. Thus, farmers participate in good access to the marketing of agricultural produce.Keywords:good governance, agrarian conflict, agricultural cooperative